2016
DOI: 10.1103/physrevb.93.115205
|View full text |Cite
|
Sign up to set email alerts
|

Polariton condensation phase diagram in wide-band-gap planar microcavities: GaN versus ZnO

Abstract: GaN and

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 61 publications
4
26
0
Order By: Relevance
“…In both GaN and ZnO systems, the minimal threshold, i.e. the minimal exciton reservoir density at condensation, is obtained at the frontier between the two regimes [25]. Moreover, the large tunability of the exciton-photon content of the obtained polariton condensates allows controlling the interaction between polaritons (i.e.…”
Section: ) Demonstrations Of Polariton Lasers At Room Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…In both GaN and ZnO systems, the minimal threshold, i.e. the minimal exciton reservoir density at condensation, is obtained at the frontier between the two regimes [25]. Moreover, the large tunability of the exciton-photon content of the obtained polariton condensates allows controlling the interaction between polaritons (i.e.…”
Section: ) Demonstrations Of Polariton Lasers At Room Temperaturementioning
confidence: 99%
“…In most works on room-temperature polariton lasing, this threshold increase related to the tightly focused excitation regime therefore plays a very important role [36,38,[48][49][50]63,85,86]. A precise investigation of the threshold excitation density as a function of the excitation spot diameter has shown that the optimal diameter of the excitation is of the order of 10 µm, for very similar GaN and ZnO microcavities [25]. The comparison between small and large spot excitations has also been explored at room temperature in the case of TDAF organic microcavities, up to 100 µm spot diameters [22,63].…”
Section: ) Demonstrations Of Polariton Lasers At Room Temperaturementioning
confidence: 99%
“…If the polariton decay rate is slower than the polariton relaxation process, it can be determined by the exciton and photon rates with weighing fraction (i. e., Hopefield coefficient, see [25]), varying along the dispersion as: The exciton-polariton composition, as a vital physical quantity for controlling the nonlinear interactions in polariton condensates [32,40], can be directly managed through cavityexcition detuning (Δ = E ph -E ex , see [25]). This detuning is most often achieved through cumbersome modification of the photon part [22,[30][31][32][33][34] due to the difficulty in controlling the exciton part.…”
Section: Two-dimensional (2d) Semiconducting Transition Metal Dichalcmentioning
confidence: 99%
“…Lett. 108, 251904 (2016) has been investigated, 18,19,21,45 can be the low growth temperature, which helps in preventing any interdiffusion between ZnO and ZnMgO thereby allowing for abrupt interfaces, and the insensitivity of the ZnO/ZnMgO surface features and roughness to the initial substrate miscut, which renders less critical the exact unintentional substrate miscut. 46 To conclude, we have introduced the growth of homoepitaxial nonpolar (10-10) monolithic ZnO/ZnMgO optical microcavities displaying flat surfaces and homogeneous Mg composition, even for micrometer-thick heterostructures.…”
Section: -4mentioning
confidence: 99%
“…The polariton disorder can largely influence the polariton condensation/lasing process, 21,22 irrespective of its actual origin. In extreme cases, where the disorder is comparable with the system Rabi splitting, it can even lead to the loss of the strong coupling.…”
mentioning
confidence: 99%